Colloidal fouling of nanofiltration membranes: A novel transient electrokinetic model and experimental study. (22nd December 2015) - Al Mamun, Md Abdullaha; Sadrzadeh, Mohtada; Chatterjee, Reeshav; Bhattacharjee, Subir; De, Sirshendu
Abstract: Fouling of nanofiltration (NF) membranes by colloidal matter is a commonly encountered phenomenon, adversely influencing the permeate quality and membrane life. In this work, a transient electrokinetic model has been developed to predict the permeate flux and observed rejection of NF membranes in presence of colloidal particles. The cake layer is considered as a swarm of non-interacting, incompressible, spherical, charged particles and the structure is represented using the cell model approach. In the cell model a single particle and a representative volume of the fluid enclosing that particle is considered. The hydrodynamic drag exerted by the stationary colloidal cake layer is obtained by the Stokes–Einstein law and combined with Kuwabara cell model to account for the effect of neighboring particles. The transport of solvent around the charged particles distorts the ionic distribution causing the development of streaming potential and electroosmotic back flow. The model provides valuable insight into application of this phenomenon in colloidal fouling of membranes, in light of the classical Levine–Neale cell model of electrophoresis. This model is then coupled with film theory to appraise the permeate flux decline and salt rejection during the filtration processes. To validate the model, cross flow NF experiment was conducted with silica particles and sodium chloride solution over a wide range of operating conditions. Graphical abstract: Swarm of non-interacting, incompressible, spherical, charged particles surrounded by a fluid envelop and distortion of ionic distribution around the charged particles due to development of electroosmotic back flow. Highlights: An electrokinetic model for colloidal fouling of nanofiltration membranes was developed. Insight to the development of streaming potential and electroosmotic back flow was provided. Transient growth of cake layer and cake enhanced concentration polarization were coupled. The transient permeate flux and observed rejection were predicted. Excellent agreement between model predictions and experimental results ( R >0.9) was observed.